The influence of income and currency changes on tourist inflow to Norwegian campsites: The case of Swedish and German visitors - Leiv Opstad; Randi Hammervold; Johannes Idsø (Economies, 2021)
There are few published articles on the demand for campsites, despite this being an important segment of the tourism industry. The purpose of this study was to gain further understanding of this topic. Using publicly available data over a period of 20 years, income and currency elasticity were estimated for German and Swedish camping tourists by using a natural logarithmic regression model with time series data. The results showed that both income and the exchange rate influenced the number of overnight stays, but the impact was rather small. The income elasticity for Swedish visitors was significant with a value of about 0.5, while it was zero and not significant for German camping tourists. Appreciation of the euro was associated with more visitors from Germany, but the estimated exchange rate elasticity was below 1.0 (and significant). A stronger Swedish currency relative to the Norwegian currency did not appear to have an effect. However, a stronger Swedish exchange rate, measured in euros, had a positive impact on Swedish camping visitors in Norway. The reason might be that more Swedish residents spend holidays abroad, and there is complementarity among the neighboring countries. Such calculations provide useful information for tourist industry planning.
Keywords: 330; campsites; demand for camping tourism; time series data; income elasticity; currency elasticity